Tourism Dynamics in Bali: A Study of Driving Factors, Challenges, and Opportunities - Luh Emik Sri Gita Noviyanti; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Jurnal Studi Perhotelan dan Pariwisata, 2025)
Purpose: This research describes the dynamics of the tourism sector in Bali Province, focusing on the factors driving tourism development, the challenges the sector faces, and the opportunities available for sustainable tourism growth. Methodology: A qualitative approach based on systematic literature review was employed, drawing on secondary data from academic articles, government reports, and news publications relevant to Bali’s tourism dynamics.Results: Cultural richness, natural beauty, and ongoing infrastructure development emerge as the primary drivers of tourism growth in Bali. Development is nevertheless constrained by environmental degradation from uncontrolled construction, over-reliance on international visitor demand that produces systemic vulnerability, and difficulty managing tourist behavior and overtourism in popular destinations. Two major opportunities are identified: sustainable tourism practices centered on environmental conservation and community empowerment, and the adoption of digital technologies for destination management, marketing, and visitor services.Conclusions: Bali’s tourism sector must balance economic growth with environmental sustainability and cultural preservation, with market diversification, sustainable governance, and digital innovation identified as priority strategies. Limitations: The study is descriptive and does not statistically test relationships among the driving factors, challenges, and opportunities identified, and proposed sustainability and digitalization measures have not been empirically validated in Bali-specific settings.Contributions: This research provides a structured analytical synthesis of Bali’s current tourism dynamics, contributing evidence-based policy insight for sustainable tourism governance in an internationally significant destination.